Evaluation of Pretrial Detention considering to the presumption of innocence and equality of arms, in the Iranian-American Legal System - hassanali moazenzadegan; hossein gholami; cyrus zarghami (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2021)
Considering the importance and effects of pretrial detention in Iran and the United States, it is important to consider the need for fair trial in this regard. In this article, in order to examine the fairness of the pretrial detention in these two countries, the presumption of innocence and equality of arms are considered as two essential principles for a fair trial as a basis. The examination of the presumption of innocence shows that the defendant's detention is not consistent with this principle, therefore, in both countries, measures such as limiting the issuance of a proceeding, the right to compensation and the right of appeal are anticipated. The study of the principle of equality of arms in this case shows that the detention of the accused is not consistent with the principle, Especially in Iran, where prosecutors can sometimes order pretrial detention. In American law, the judge who is neutral can issue this order. In both countries, there is a right of access to a lawyer in order to strengthen the defense rights of the accused at the time of his detention.